ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN PENERAPAN METODE HARGA POKOK PENUH PADA ROTI GEMBONG BONGSOR KARAWANG - Nadya Millasyifa; Luthfi Thoriq Amalia; Hilman Muhamad Naufal; Mohamad Hafizh Enriza; Lizha Nur Shafa; Tiar Lina Situngkir (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2022)
This study aims to analyze the comparison of the Cost of Goods Sold based on the Small and Medium Enterprises (SME) Method of Roti Gembong Bongsor and the full costing method. The method of data collection applied in this research is by observation and personal interviews with SME owners as people who provide the information and data that researchers needs. The results of the research that has been carried out show that the resulting production costs consist of raw material costs of Rp 5,967,000, direct labor costs of Rp 15,000,000, variable factory overhead costs of Rp 9,123,500, and fixed overhead costs of Rp 5.234.997. This study shows that the results of calculating the cost of goods sold using the full costing method produce a higher price than the SME method.